Contextualization of the meaning of the story of Ashabul Fil in QS. Al-Fil perspective al-Fann al-Qashasi Khalafullah - Rohman, Taufiqur; Kharomen, Agus Imam; Muhammad, Hayim (Universitas Muhammadiyah Surakarta, 2026)
This study analyzes the narrative of Ashābul Fīl in Surah al-Fīl through Muhammad Ahmad Khalafullah's al-fann al-qashāṣī framework. While classical exegesis largely emphasizes the historical dimension of the event, limited research systematically applies Khalafullah's literary-narrative approach to short Makkiyyah surahs. This study addresses that gap by examining the aesthetic structure, symbolism, and theological meaning of QS. al-Fīl beyond historiographical concerns. Using a qualitative-descriptive design with a literary-hermeneutic approach, the research is based on textual analysis of the Qur'an, classical and modern tafsīr, and Khalafullah's theoretical works. Narrative structural analysis and thematic interpretation are employed to identify symbolic and theological patterns within the text. The findings show that QS. al-Fīl presents a dramatic structure consisting of threat, divine intervention, and the destruction of tyranny. The symbols of ṭayran abābīl and ḥijārah min sijjīl function as theological metaphors representing divine sovereignty and moral accountability. This study demonstrates that Khalafullah's approach enriches contemporary Qur'anic interpretation by integrating aesthetics, symbolism, and theology. Globally, the research highlights the Qur'an's ethical relevance in addressing injustice, authoritarianism, and moral crisis in modern society.